Telegram from George Louis to Howard Louis, December 24, 1928 [telegram and envelope] - George Louis::::::author::: (1928)
Text of telegram reads: 'Howard Louis. Am wishing a merry Xmas and happy New Year to Papa May Ed Stella Young Elsie Billy Eddie and yourself. Many thanks for the jerkey and also Billy and Eddie for the underwear you kids shouldnt have bothered and saved your money, hope Papa receives money, am writing regards, George.' Envelope depicts a trio of musicians next to the words 'Holiday Greetings, Western Union'. Back of telegram envelope reads: 'It is not too late to answer Holiday Greetings by telegraph'